Catheter-Based Computed Tomography Angiography in Anterolateral Thigh Perforator Mapping of Chinese Patients - Wang, Zhongjie; Yi, Xiaoping; He, Jiqiang; Qing, Liming; Zhou, Zhengbing; Zhang, Youming; Zhu, Zhiming; Zhou, Chunhui; Xie, Hui; Li, Xuejun; Zee, Chishing; Chen, Bihong T. (Journal of Reconstructive Microsurgery, 2019)
Background During reconstructive surgery, anterolateral thigh (ALT) flap harvest is challenging due to variation and uncertainty in perforator distribution. We performed a pilot study to identify the predictive value of catheter-based computed tomography angiography (C-CTA) and traditional CTA (T-CTA) in ALT perforator mapping for patients whose ALT perforators were difficult to identify.Methods Thirty-four consecutive T-CTA/C-CTA-mapped ALT flaps were evaluated for extremity reconstruction. The perforator location, origin, and course were compared between T-CTA/C-CTA imaging and intraoperative findings. The mapping efficiency of T-CTA and C-CTA was compared thoroughly.Results Among the 34 ALT thigh flaps, 117 (36) of the 130 perforators identified intraoperatively were visible on C-CTA (T-CTA) in a subgroup of Chinese limb trauma patients with limited activity. C-CTA showed a satisfactory efficiency in perforator mapping, which was much better than the efficiency of T-CTA. C-CTA also showed a much better sensitivity (90.00 vs. 27.69%), specificity (94.74 vs. 66.67%), and accuracy (91.07 vs. 36.69%), and a much lower false-positive (1.68 vs. 26.53%), and false-negative rate (10.00 vs. 72.31%). Moreover, C-CTA could accurately predict the origin and septocutaneous or intramuscular course in all identified perforators. All flaps were elevated successfully and survived.Conclusion C-CTA outperforms T-CTA in the preoperative perforator mapping of ALT flaps in a subgroup of Chinese limb trauma patients. C-CTA should be the method of choice for perforator mapping in patients whose ALT flaps are intended for extremity reconstruction.
Keywords: CT angiography; catheter-based CTA; anterolateral thigh flap; perforator mapping; reconstructive surgery; limb trauma; digital subtraction angiography